Validity of Learning Video Media with an Open-Ended Approach to Mathematics Learning Outcomes - Henry Suryo Bintoro; Baron Adi Wijaya; Sumaji (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The purpose of this study was to analyze the validity of the design of the development of learning video media with an open-ended approach to improve the learning outcomes of 6th-grade elementary school students in Mlonggo District. This study applies the research and development method, which is commonly known as R&D (Research and Development). Products development uses the ADDIE model which is structured into five stages including (1) analysis, (2) design, (3) development, implementation, and (5) evaluation. Data collection through filling out the validity questionnaire. This data source includes participation from data validators with an analysis process that includes the accumulation of overall scores. Data analysis uses descriptive qualitative tests. The results of this development research are learning video media with an open-ended approach which is stated to be very feasible by media experts with an average of 90%, and material experts with 92%. So, it can be concluded that learning video media with an open-ended approach is valid and feasible to be used to improve student learning outcomes